A Malignant Squeeze: A Rare Cause of Cardiac Tamponade - Elisa Quiroz; Adam Hafeez; Ramy Mando; Zhou Yu; Feroze Momin (Case Reports in Oncological Medicine)
Primary cardiac lymphoma (PCL) is a rare condition described as a lymphoma localized to the heart or pericardium. Although cardiac involvement is seen in 10–20% of non-Hodgkin’s lymphomas, PCL is extremely rare. It comprises merely 0.5% of all lymphomas and 1.3–2% of cardiac malignancies. Early detection is essential to avoid potentially fatal complications, and prognosis is highly dependent on the management of cardiac complications. The etiology of PCL is still unknown, and molecular characterization has yet to be studied leaving a great deal of research to be done in order to gain a better understanding of this rare disease process. We discuss the case of an 85-year-old female presenting with dyspnea and chest pain. Computed tomography of the chest revealed a pericardial effusion, and subsequent echocardiogram demonstrated a large circumferential effusion. She underwent emergent pericardiocentesis. Morphologic and immunophenotypic features were consistent with high-grade B-cell lymphoma with t8;14, and the patient was started on rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) with excellent response.